Development of Geometry Test Based on Van Hiele's Theory in Exploration Profile of Student's Spatial Reasoning Ability Level - Komala Komala; Budi manfaat; Arif Abdul Haqq (EduMa: Mathematics education learning and teaching, 2021)
Assessment of geometry learning should encourage students to have spatial reasoning abilities. This type of study is research and development to develop a geometry test instrument with Van Hiele's level of thinking to measure students' spatial reasoning abilities. This research and development aim to obtain a valid and reliable test instrument for spatial reasoning abilities. This test has been declared content validity through expert judgment techniques and has been declared linguistically correct by linguists. Based on the results of the field test, the test instrument has a reliability of 0.89. The developed test instrument has a pretty good average distinguishing power estimate. The results of the difficulty level of the developed test are 12.5% items have a very easy, 25% easy, 37.5% moderate, and 25% difficult. The results of the measurement of students' spatial reasoning ability obtained that 25% of students had low spatial reasoning abilities (Plane), 60.71% in the medium category (Fuzzy), and 14.29% in the high category (Spatial)Â